Research Trends on the Acupuncture treatment for Delayed Onset Muscle Soreness - Min Geon Lee; Eun Ji Oh; Han Eung Jo; Hyang Gi Lim; Sang Ha Woo; Yun Kyu Lee; Hyun-Jong Lee; Jae Soo Kim; Jung Hee Lee (Journal of Korean Medicine, 2026)
Objectives: This study aimed to analyze research trends in randomized controlled trials (RCTs) of acupuncture for delayed-onset muscle soreness (DOMS) published from January 2000 to December 2025.Methods: Seven electronic databases were searched for eligible RCTs. Data on publication characteristics, participants, DOMS induction methods, interventions, outcome measures, results, and adverse events were extracted and analyzed descriptively.Results: Nine RCTs involving 270 participants were included. Most participants were young, healthy adults with experimentally induced DOMS. The biceps brachii and triceps surae were the most commonly targeted muscles. Acupuncture protocols, comparator interventions, assessment time points, and outcome measures varied across studies. Five of the seven studies using a visual analogue scale reported significantly lower pain scores in the acupuncture groups than in the control groups, mainly 24–72 hours after exercise. Findings for pressure pain threshold, muscle strength, range of motion, exercise performance, and serum creatine kinase were inconsistent or generally nonsignificant. Reporting of acupoint selection, needling procedures, and adverse events was incomplete. Only one study explicitly reported the absence of adverse events.Conclusions: Existing RCTs have focused mainly on pain-related outcomes. Although reductions in subjective pain were frequently reported, findings for objective functional and biochemical outcomes were inconsistent. Future studies should improve comparability and reproducibility by clearly reporting DOMS induction methods, acupuncture procedures, comparator interventions, assessment time points, and adverse events and by evaluating both pain and objective functional recovery.